Shifting the learning gears: Redesigning a project-based course on soft matter through the perspective of constructionism - Elon Langbeheim (American Physical Society, 2020)
This article describes the redesign of a project-based course on soft and biological materials to include computational modeling. Including the construction of computational models in the course is described as a shift from constructivism—a theory that characterizes the development of formal reasoning, to constructionism—a theory that focuses on learning while constructing artifacts. This shift ameliorated two drawbacks in the original course: the limited conceptualization of entropy resulting from an unproductive use of the disorder metaphor, and the dependence of most students on the teacher for writing theoretical explanations for their final papers. In the redesigned curriculum, computer simulations provide concrete dynamic representations that students can draw upon for developing nuanced, formal reasoning on entropy and the 2nd law of thermodynamics. In addition, core computational models act as a flexible web that can be extended and modified, and allow a significant proportion of the students to build theoretical models on their own. We conclude that while the new design reflects a shift towards constructionism, we did not adopt a fully constructionist approach, rather a blend of constructivist and constructionist approaches.